The Stature of the Journal of International Business Studies - Phene, Anupama; Guisinger, Stephen (Journal of International Business Studies, 1998)
This article examines the standing of the Journal of International Business Studies (JIBS) among scholarly journals, and changes in its influence, over a 11 year period (1981 to 1991) using a variety of citation indices. We suggested that two new measures—a prestige index and a trajectory index—are helpful in assessing a journal's influence and reputation. We estimate these, as well as several standard citation measures, to gauge JIBS' progress in the recent past. We find that JIBS does well on all measures, but room for improvement remains. This article discusses options available to the editorial board to raise JIBS' prestige.